Determination of 21 drugs in oral fluid using fully automated supported liquid extraction and UHPLC‐MS/MS. Issue 5 (19th August 2016) - Valen, Anja; Leere Øiestad, Åse Marit; Strand, Dag Helge; Skari, Ragnhild; Berg, Thomas
Abstract : Collection of oral fluid (OF) is easy and non‐invasive compared to the collection of urine and blood, and interest in OF for drug screening and diagnostic purposes is increasing. A high‐throughput ultra‐high‐performance liquid chromatography‐tandem mass spectrometry method for determination of 21 drugs in OF using fully automated 96‐well plate supported liquid extraction for sample preparation is presented. The method contains a selection of classic drugs of abuse, including amphetamines, cocaine, cannabis, opioids, and benzodiazepines. The method was fully validated for 200 μL OF/buffer mix using an Intercept OF sampling kit; validation included linearity, sensitivity, precision, accuracy, extraction recovery, matrix effects, stability, and carry‐over. Inter‐assay precision (RSD) and accuracy (relative error) were <15% and 13 to 5%, respectively, for all compounds at concentrations equal to or higher than the lower limit of quantification. Extraction recoveries were between 58 and 76% (RSD < 8%), except for tetrahydrocannabinol and three 7‐amino benzodiazepine metabolites with recoveries between 23 and 33% (RSD between 51 and 52 % and 11 and 25%, respectively). Ion enhancement or ion suppression effects were observed for a few compounds; however, to a large degree they were compensated for by the internal standards used. Deuterium‐labelled and 13 C‐labelled internal standards were used for 8 and 11 of the compounds, respectively. In a comparison between Intercept and Quantisal OF kits, better recoveries and fewer matrix effects were observed for some compounds using Quantisal. The method is sensitive and robust for its purposes and has been used successfully since February 2015 for analysis of Intercept OF samples from 2600 cases in a 12‐month period. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A UHPLC‐MS/MS method for the determination of 21 drugs in oral fluid using fully automated 96‐well plate supported liquid extraction for sample preparation was developed and fully validated. Deuterium‐labelled and 13 C‐labelled internal standards were used for 8 and 11 of the compounds, respectively. Extraction time for 96 samples was 1.5 h, and validation showed that the method is accurate, precise, and robust for its purposes.